Alkaline proteinase in muscle of commercial fishes - Pangkey, Henneke; Rimper, Joice R.S.T.L; Kemer, Kurniati (Universitas Sam Ratulangi, 2013)
Sea products are valuable resources of natural substances such as lipids, polysaccharides, enzymes, vitamins, and proteins. Fish proteases have been characterized and some purified. Many of these enzymes display potentially interesting new biochemical properties for biotechnological applications. In this research, we have found activity of some proteases (alkaline proteinase, cathepsin S and cathepsin D) in muscle tissues of marine tropical commercial fish species in North Sulawesi (i.e. Epinephelus fuscoguttatus, Caranx ferdau, Lutjanus malabricus, and Katsuwonus pelamis). All of these fish are economical species with low prices that are highly consumed by local peopleÂ©Produk yang berasal dari laut merupakan sumberdaya yang kaya akan bahan-bahan alamiah seperti lipida, polisakarida, enzim, vitamin dan protein. Beberapa enzim protease pada ikan telah diidentifikasi dan dimurnikan. Banyak dari enzim ini menunjukkan potensi yang penting sebagai bahan biokimia yang baru. Pada penelitian ini, kami menemukan beberapa jenis protease (alkalin proteinase, katepsin S dan katepsin D) yang aktif pada otot dari beberapa jenis ikan laut tropis yang komersil di Sulawesi Utara (Epinephelus fuscoguttatus, Caranx ferdau, Lutjanus malabricus, and Katsuwonus pelamis). Ikan-ikan ini sangat bernilai ekonomis dan sangat digemari oleh masyarakat lokalÂ©